Peran Intelektual Capital dalam Memediasi Pengaruh Inovasi terhadap Kinerja Industri Kecil Menengah (IKM) Kabupaten Wonosobo - Muhamad Asif Maulana Akbar; Bahtiar Efendi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to examine the effect of innovation on intellectual capital, examine the effect of innovation on performance, examine the effect of intellectual capital on performance, and test the effect of innovation on the performance of IKM in Wonosobo Regency which is mediated by intellectual capital. This study uses a quantitative method with two kinds of data used, namely (1) primary data, as main data and (2) secondary data, as supporting data. For this study, the population used as the population was the owners of SMIs in Wonosobo Regency at the end of 2022. The population in this study was 225 SMIs in Wonosobo Regency. The criteria stipulated in the sample selection are IKMs that fulfill a complete business license which includes SIUP, TDP, NPWP. From the existing data as many as 168 samples that have met the criteria to be a sample. The respondents in this study were IKM owners. Based on the results of the analysis and discussion in this study, it was concluded that innovation has an effect on intellectual capital, innovation has an effect on performance, intellectual capital has an effect on the performance of IKM Wonosobo Regency, and intellectual capital mediates the influence of innovation on the performance of IKM Wonosobo Regency.